A change of view: Homologous recombination at single-molecule resolution - Kaniecki, Kyle (2018)
Genetic recombination occurs in all organisms and is vital for genome stability. Indeed, in humans, aberrant recombination can lead to diseases such as cancer. Our understanding of homologous recombination is built upon more than a century of scientific inquiry, but achieving a more complete picture using ensemble biochemical and genetic approaches is hampered by population heterogeneity and transient recombination intermediates. Recent advances in single-molecule and super-resolution microscopy methods help to overcome these limitations and have led to new and refined insights into recombination mechanisms, including a detailed understanding of DNA helicase function and synaptonemal complex structure. The ability to view cellular processes at single-molecule resolution promises to transform our understanding of recombination and related processes.